AGE-FRIENDLY INITIATIVES AND IMMIGRANT SENIORS: ADDRESSING SOCIAL ISOLATION USING TECHNOLOGY. (11th November 2018) - Mirza, R; Liu, A; Klinger, C
Abstract: Of the eight dimensions of the World Health Organization's "age-friendly" cities initiative, the communication domain highlights the importance of information about community events and services being available in formats that are 'appropriate' for older adults. Although older immigrants may face pervasive language barriers in the English-speaking communities they often reside in, various forms of technology show promise for bridging communication deficits and reducing social isolation. To better understand the role of technology for facilitating communication, a mixed-methods study consisting of surveys (n=100) and two focus groups led by native language speakers were conducted with Cantonese (n=6) and Mandarin speaking (n=19) seniors (65+) living in Chinatown, Toronto, Canada. The surveys used standardized scales for social participation to measure aspects of the seniors' lived experiences including sense of belonging, availability and access to community/ healthcare services, frequency and quality of family and social interactions, and perceived personal well-being. Both quantitative and qualitative findings indicate that technology was favoured as a primary method of communication for immigrant seniors, and that this mode of communication can facilitate significant improvement in multiple domains of age-friendly initiatives including: social participation and inclusion, community support and health services, and transportation. To maximize the use of tangible and tech-based resources available to seniors (i.e., wearables, smartphones), communities should incorporate technology such as messaging apps or electronic translation services to instantly mobilize information and knowledge into accessible language and cultural formats. Circumventing language barriers with other seniors and service providers in the community, technology may promote greater social participation.